Non-Penal Efforts in Achieving Restorative Justice For The Prevention of Violent Crimes For Children Who Are in Conflict With The Law As Victims of Domestic Violence - Rahayuningsih, Uut (Faculty of Law, Universitas Pekalongan, 2024)
Domestic violence often results in children being victims. Home is supposed to be the safest and most comfortable place for a person, but it is the opposite where children often get violence from the family. In the city of Samarindah, cases of domestic violence have increased every year, namely in 2020 there were 154 cases with a total of 161 victims with details of 65 men and 96 women, in 2021 there were 133 cases with a total of 146 victims with 35 men and 111 women, in 2022 there were 182 cases with a total of 188 victims with 63 men and 125 women, And in 2023 there will be 189 cases with a total of 230 victims with details of 93 men and 137 women. The research that has been carried out is legal normative research that focuses on norms and also legal objects as the main data. The formulation in this study is what are the non-penal efforts in achieving restorative justice for the prevention of violent crimes for children facing the law as victims of domestic violence, factors that affect the occurrence of violent crimes against children, and how the implementation of non-penal efforts in achieving restorative justice for the prevention of violent crimes against children facing the law as victims of domestic violence.The results of this research are non-penal efforts in achieving restorative justice for the handling of violent crimes for children as victims of domestic violence in such as prioritizing restorative justice, factors that affect the occurrence of violence usually due to economic factors, and the implementation of this non-penal effort can be carried out preemptively and preventively.